Combination decoction of Astragalus mongholicus and Salvia miltiorrhiza mitigates pressure-overload cardiac dysfunction by inhibiting multiple ferroptosis pathways - Xu, Qiyao; Liu, Xuan; Chen, Zhaoyang; Guo, Can; Lu, Pengyu; Zhang, Sujie; Wang, Xindong; Shen, Jianping (Frontiers in Pharmacology, 2024)
Background Astragalus mongholicus (AM) and Salvia miltiorrhiza (SM) are commonly used in traditional Chinese medicine to treat heart failure (HF). Ferroptosis has been studied as a key factor in the occurrence of HF. It remains unclear whether the combined use of AM and SM can effectively improve HF and the underlying mechanisms. Objective This study aims to explore whether the combined use of AM and SM can improve HF by inhibiting ferroptosis. It also examines the roles and interactions of the pathways associated with GPX4, FSP1, and DHODH. Methods In vitro experiments used angiotensin II-induced (4 μM for 48 h) hypertrophic H9c2 cells, while in vivo studies employed a rat model of transverse aortic constriction-induced (to 1 mm for 8 weeks) HF. Interventions included decoctions of AM and SM (for animal experiments) and medicated serum (for cell experiments), along with specific pathway inhibitors such as erastin, FSP1 inhibitor and brequinar. Subsequently, various molecular biology methods were used to measure the protein levels of GPX4, FSP1, and DHODH, as well as each sample group’s ferroptosis-related and HF-related indicators, to elucidate the underlying mechanisms. Results The combined use of AM and SM can effectively restore the levels of GPX4, FSP1, and DHODH that are reduced after HF, as well as improve indicators related to ferroptosis and HF. When GPX4, FSP1, or DHODH is inhibited, the ferroptosis-inhibiting effect and the ability of AM and SM to improve HF are both weakened. When two of the three proteins are inhibited, the protective effect of HDC is strongest when GPX4 is retained, followed by FSP1, and weakest when DHODH is retained. Conclusion This study confirms that the combined use of AM and SM inhibits ferroptosis and alleviates HF by increasing GPX4, FSP1, and DHODH levels. It shows that the protective effect is strongest through GPX4, followed by FSP1, and weakest through DHODH. These findings provide new insights into the therapeutic mechanisms of this combination of botanical drugs.